2009
DOI: 10.1111/j.1365-2559.2009.03301.x
|View full text |Cite
|
Sign up to set email alerts
|

The matrix metalloproteinase/tissue inhibitor of matrix metalloproteinase profile in colorectal polyp cancers

Abstract: This study defines the expression profile of MMPs and TIMPs in colorectal polyp cancers and shows that the increased expression of MMPs and TIMPs occurs at an early stage of colorectal neoplasia. It provides evidence to support the hypothesis that these molecules have a key involvement in the early stages of tumour development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 40 publications
5
22
0
Order By: Relevance
“…MMP-7 is widely expressed in the epithelial tumor cells of malignant colorectal adenocarcinomas and believed to be associated with metastasis [13] [14] [30] [31]. In the current study we found that MMP-7 was overexpressed in 38.8% of CRCs and this positive rate is comparable with previous reports of 30% to 46% [15] [17] [30] [32]. In a recent study with a larger sample size of 620 cases, Fang et al reported MMP-7 immunopositivity in 88.8% of the cancer [33].…”
Section: Discussionsupporting
confidence: 90%
“…MMP-7 is widely expressed in the epithelial tumor cells of malignant colorectal adenocarcinomas and believed to be associated with metastasis [13] [14] [30] [31]. In the current study we found that MMP-7 was overexpressed in 38.8% of CRCs and this positive rate is comparable with previous reports of 30% to 46% [15] [17] [30] [32]. In a recent study with a larger sample size of 620 cases, Fang et al reported MMP-7 immunopositivity in 88.8% of the cancer [33].…”
Section: Discussionsupporting
confidence: 90%
“…(p=0.42) Discussion MMP-3 is an element of MMP system which performs a substantial role in apoptosis induction, angiogenesis, regulation of tumor growth, invasion and metastasis in cancer. These functions are known to be the fundamental changes in cancer physiology (Egeblad M, Werb Z,2002) .Pathologic appearance of MMP-3 has been found in many cancers (Linkow et al, 2007;Gershtein et al, 2008;Tas et al, 2008;Jeffery et al, 2009;Yeh et al, 2010). Most of investigators on SCC had construed high expression of MMP-3 in patients compared to control groups (Kusukawa et al, 1995;Kurahara et al, 1999;Baker et al, 2006;Vairaktaris et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The role of MMP-3 in apoptosis induction, angiogenesis regulation, invasion and metastasis in cancer has been established. MMP-3 reveals pathological expression in many tumors; such as melanoma, skin squamous cell carcinoma, colorectal neoplasia, gastric cancer, head and neck squamous cell carcinoma (HNSCC) and breast cancer (Tsukifuji et al, 1999;Linkow et al, 2007;Gershtein et al, 2008;Tas et al, 2008;Jeffery et al, 2009;Yeh et al, 2012). MMP-3 expression has been used as an impending diagnostic and/ or prognostic marker of some cancers (Fang et al, 2005;Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor in the tumour invasion and metastasis process is the matrix metalloproteinase (MMP)/tissue inhibitor of metalloproteinase (TIMP) system. There are differences in the expression of MMP/TIMP between benign and malignant lesions (Jeffery et al 2009), and MMP activity can be detected in cancer cells before the detection of extravascular metastasis (Zhang et al 2010). The expression of MMP2 in pancreatic NETs (particularly in gastrinomas) could be used to characterise a malignant phenotype, whereas weak expression of MMP9 could indicate a less invasive phenotype (Gurevich 2003).…”
Section: Activating Invasion and Metastasismentioning
confidence: 99%